Right pneumothorax with congenital pericardial defect showed right atrium mimicking bulla in surgery - Yasoo Sugiura; Toshinori Hashizume (Surgical Case Reports)
Abstract Background Congenital pericardial defect (CPD) is found incidentally in cases of pneumothorax. CPD is seen in left side rather than right side and it is not generally known among thoracic surgeons how the inside of the pericardial space can be seen from the thoracic cavity in cases of pericardial defect. Case presentation A 52-year-old man with dyspnea was referred to our hospital because of the diagnosis of right pneumothorax. Chest radiography showed a right lung collapse and a pneumopericardium on the left side. Despite insertion of a chest tube, air leakage prolonged, bullectomy at the apex of the right lung was performed under thoracoscopy. During surgery, thoracoscope showed that the right atrium seemed as if it had been a non-pedunculated bulla or cardiac cyst. Heart beating, continuity with the heart, and the absence of respiratory motion could distinguish the right atrium from a bulla, and pericardial defect was confirmed. Preoperatively, the patient had no cardiac symptoms related to the CPD, and therefore, it was determined that a procedure to close the CPD was not necessary. Any complication and recurrence did not occur 6 months after surgery. Conclusions Right pneumothorax with CPD showed right atrium mimicking bulla in surgery. It is important to consider correction of CPD if there are cardiac symptoms at the onset of pneumothorax, and not to misinterpret the right atrium as a bulla.